Time Synchronization at OS Level Using the IEEE 1588 Protocol - Oliveira, Peterson; Okazaki, Alexandre Massayuki; Fröhlich, Antônio Augusto (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC); 2012: Anais do II Simpósio Brasileiro de Engenharia de Sistemas Computacionais, 2012)
Time Synchronization is a pertinent field of study to fulfill the OS requirements in many distributed applications. In this work, we implemented the IEEE 1588 protocol - Precision Time Protocol - for the EPOS operating system to deliver the clock time among the network. For test purposes, we choose a topology consisted of one master clock and another slave clock. We made two configurations: one in which we have two previously synchronized clocks, to evaluate their behavior among time after some synchronizations. On the other configuration, we delayed the slave clock in some hours and analysed the behavior of the protocol after some iterations. With the results obtained we can ensure the viability of the protocol implementation to the EPOS operating system and consequently to embedded systems.